Investigation of the Return and Volatility Clustering Effects in China Stock Markets - Mei, Lirong (2009)
This dissertation examines the return and volatility in Shanghai Stock Exchange (SSE); Shenzhen Stock Exchange (SZSE); Hong Kong Stock Exchange (HKEx) and Taiwan Stock Exchange (TWSE) in China for the period Jan 2002-Dec 2008 employing the GARCH models. GARCH-M; TGARCH-M and EGARCH-M model are estimated using three return intervaldaily; weekly and monthly. The results confirmed the leverage effects in these stock markets; but the significance of the estimation are questioned partly for the insufficient data in low frequency intervals. Comparison between the three models concluded with the superiority of the EGARCH over the other two models. Misspecification testing and Granger Causality Test are employed for modification of the model and examination of the spillover effect in the markets. ARMA lag specification in mean equations are suggested for the modification of the models; inclusion of GARCH variance lag terms in the variance equation also recommended for the models of the markets that have spillover effect between or from other markets.